2017
DOI: 10.3390/lubricants5030027
|View full text |Cite
|
Sign up to set email alerts
|

Time-Resolved Characterization of Dynamic Tribochemical Processes for Dicationic Imidazolium Ionic Liquid

Abstract: Dynamic tribochemical processes for dicationic ionic liquid containing a geminal imidazolium cation head group bridged by a poly(ethylene glycol) and a bis(trifluoromethylsulfonyl)imide anion were studied using time-resolved mechanically stimulated gas emission mass-spectrometry (MSGE-MS). In comparison with similar monocationic imidazolium ionic liquids with short alkyl or long polyether side chains, the dicationic ionic liquid had a lower coefficient of friction on Ti6Al4V alloy and smoother behavior. The an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…valence ratio 2:1) are particularly favourable for tribological applications because of their high decomposition temperature 15,16 and good anti-wear performance, especially at higher temperatures. [17][18][19][20][21][22][23] While several studies have measured the lubrication response of 1:1 ionic liquids in the boundary regime, [11][12][13][24][25][26] the friction response of nanoconfined ionic liquids with ions of higher valencies remains largely unexplored. 20 The structure of nano-scale films of 2:1 ionic liquids might be expected to differ from that of 1:1 ionic liquids, and this should -in turn -lead to variation in the dynamic properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…valence ratio 2:1) are particularly favourable for tribological applications because of their high decomposition temperature 15,16 and good anti-wear performance, especially at higher temperatures. [17][18][19][20][21][22][23] While several studies have measured the lubrication response of 1:1 ionic liquids in the boundary regime, [11][12][13][24][25][26] the friction response of nanoconfined ionic liquids with ions of higher valencies remains largely unexplored. 20 The structure of nano-scale films of 2:1 ionic liquids might be expected to differ from that of 1:1 ionic liquids, and this should -in turn -lead to variation in the dynamic properties.…”
Section: Introductionmentioning
confidence: 99%
“…These favorable traits are leading to incorporation of ionic liquids in many technological directions, and here we focus on their increasing use as lubricants. In particular, it has been demonstrated that dicationic ionic liquids (with monovalent anion, i.e., valence ratio 2:1) are particularly favorable for tribological applications because of their high decomposition temperature , and good antiwear performance, especially at higher temperatures. While several studies have measured the lubrication response of 1:1 ionic liquids in the boundary regime, , the friction response of nanoconfined ionic liquids with ions of higher valencies remains largely unexplored . The structure of nanoscale films of 2:1 ionic liquids might be expected to differ from that of 1:1 ionic liquids, and this should–in turn–lead to variation in the dynamic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Such behaviour is typical for depleting emission sources. 34 The driving forces for such gas emission must be directly linked to mechanical action. In contrast, the emission of H 2 first leapt down to a certain non-zero value and then continued to decay for thousands of seconds forming a characteristic trail (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The gas composition and the emission rates were determined using a previously developed statistical matrix method. [32][33][34] If not stated otherwise, each test was carried out on a pristine surface zone.…”
Section: Materials and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation